The implications of optional practical training reforms on international student enrollments and quality. (30th November 2022) - Amuedo‐Dorantes, Catalina; Shih, Kevin; Xu, Huanan
Abstract: The Optional Practical Training (OPT) program allows international students to work temporarily in the United States during or directly following their studies. In 2008 the work duration was extended for eligible STEM majors, and in 2011 and 2012 the list of eligible majors was expanded. Using administrative records, we examine how these reforms impacted the enrollment and quality of international students. OPT reforms raised matriculation of international students in bachelor's and master's programs by 18% and 30%, respectively. Additionally, they improved the quality of students, as exemplified by greater scholarship/fellowship funding and matriculation into highly selective universities.